The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s0085-56262012005000027
|View full text |Cite
|
Sign up to set email alerts
|

Gafanhotos (Orthoptera, Acridoidea) em áreas de cerrados e lavouras na Chapada dos Parecis, Estado de Mato Grosso, Brasil

Abstract: Revista Brasileira de Entomologia 56(2): 228-239, junho, 2012 O Cerrado, bioma característico do Planalto Central, com grande diversidade de flora e de fauna, foi incluído na lista dos hotspots em diversidade do planeta pela Conservation Internacional (Mittermeier et al. 1999) devido a ameaças que vem sofrendo em virtude da ação do homem. As diminuições territoriais deste bioma ocorridas ao longo dos anos, em especial a partir da década de 1980, tem se tornado uma preocupação da comunidade científica.Vários… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
(28 reference statements)
0
4
1
4
Order By: Relevance
“…Compared to other such studies in Brazil (Costa & Jantsch 1999;Lutinsk et al 2011;Guerra et al 2012) and in South America (Cigliano et al 2000;Torrusio et al 2002), the diversity of grasshoppers observed in the present study is high. Forty-six species were identified, with the richest family being Acrididae, with 39 (85%) of the species collected.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Compared to other such studies in Brazil (Costa & Jantsch 1999;Lutinsk et al 2011;Guerra et al 2012) and in South America (Cigliano et al 2000;Torrusio et al 2002), the diversity of grasshoppers observed in the present study is high. Forty-six species were identified, with the richest family being Acrididae, with 39 (85%) of the species collected.…”
Section: Discussioncontrasting
confidence: 93%
“…However, recent studies have identified a number of species of subfamily Gomphocerinae (Lutinsk et al 2011;Guerra et al 2012). Lutinsk et al (2011) found 25 species in the Chapecó National Forest Reserve in the state of Santa Catarina (southern Brazil).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A grande ocorrência de Acrididae é explicada por se tratar da família que possui a maior riqueza entre os ortópteros, com 6.576 espécies, e a que possui os gafanhotos encontrados com maior frequência nos ambientes naturais, tais como observado em estudos realizados no Cerrado (GUERRA et al, 2012), na Amazônia (NUNES-GUTJAHR; BRAGA, 2010, 2015) e em áreas de fragmentos florestais e de cultivares no Sul do Brasil (LUTINSKI et al, 2011).…”
Section: Resultsunclassified
“…Dentro de Acrididae, a espécie Abracris dilecta Walker, 1870 foi encontrada como a de maior abundância relativa nos cerrados, dentro da subfamília Ommatolampidinae (Guerra et al 2012), são comumente encontrados em limites florestais abertos, ambientes secos, arbustivos e associados a plantas cultivadas, bem como com Bromeliaceae (roBerts & CarBoNell 1981) e mais14 espécies de plantas nas famílias Asteraceae, Lamiaceae, Malvales (Sterculiaceae, Tiliaceae, Malvaceae), Poaceae, Fabaceae, Verbenaceae, Aristolochiaceae, Rubiaceae e Melastomataceae, apresentando portanto características biológicas de espécie generalista (sperBer 1996). Sua distribuição na América do Sul ocorre entre Bolívia, Colômbia, Uruguai, México, Argentina e Brasil (Pará, Mato Grosso, Mato Grosso do Sul, Rio Grande do Sul, Santa Catarina e Paraná).…”
Section: Conforme Descrito Porunclassified